If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14x + -19 = (52x) + -95 Reorder the terms: -19 + 14x = (52x) + -95 Reorder the terms: -19 + 14x = -95 + (52x) Solving -19 + 14x = -95 + (52x) Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '(-52x)' to each side of the equation. -19 + 14x + (-52x) = -95 + (52x) + (-52x) Combine like terms: 14x + (-52x) = -38x -19 + -38x = -95 + (52x) + (-52x) Combine like terms: (52x) + (-52x) = 0 -19 + -38x = -95 + 0 -19 + -38x = -95 Add '19' to each side of the equation. -19 + 19 + -38x = -95 + 19 Combine like terms: -19 + 19 = 0 0 + -38x = -95 + 19 -38x = -95 + 19 Combine like terms: -95 + 19 = -76 -38x = -76 Divide each side by '-38'. x = 2 Simplifying x = 2
| x+3x+4=24 | | 3(x+1)-4(y-1)=13 | | (4x-7)/4 | | -.08x-.19=-.12x+.11 | | 4xy+7xy+6xsquaredy+7xysquared= | | 2(x-3)+2x=4(x+6)-30 | | 4xy+7xy+6xsquaredy+7xysquared= | | 4(-7+5q)= | | 10x+5x+15=60 | | 7(x-8)=2(x+22)+940 | | 3[7-2(-4-1)]= | | -8x-8+3(x-2)=3x+2 | | 1/3(6h+15) | | 3(k+8)=5k+8-2k | | 26-7x=8-4x | | 8v-6=-v+6(v-3) | | 50000=190000-.92X | | 20+-14= | | (2x^2+3x)(25x^2-5x-2)=0 | | 3y+9=3 | | -24u=u | | 2x+2x+4=14 | | -5(-7r+4)= | | 5500+4b=15b | | (6-t-t^4)+(9t+t^4)=0 | | 8x-4=64 | | 10+-7+10+-7= | | 9+3x=4x | | 1/2(10x-2)+3x=-25 | | 3n+2n+5=50 | | .6x-.7=x-5.2 | | 14-3.2w=76.24 |